2011
DOI: 10.1128/aem.01219-10
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose- and Xylan-Degrading Thermophilic Anaerobic Bacteria from Biocompost

Abstract: Nine thermophilic cellulolytic clostridial isolates and four other noncellulolytic bacterial isolates were isolated from self-heated biocompost via preliminary enrichment culture on microcrystalline cellulose. All cellulolytic isolates grew vigorously on cellulose, with the formation of either ethanol and acetate or acetate and formate as principal fermentation products as well as lactate and glycerol as minor products. In addition, two out of nine cellulolytic strains were able to utilize xylan and pretreated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(65 citation statements)
references
References 44 publications
2
62
1
Order By: Relevance
“…S-2). This phenotype is different from several previously described xylanfermenting thermophiles such as C. thermolacticum (Le Ruyet et al, 1985) and C. clariflavum (Sizova et al, 2011).…”
Section: Identification and Characterization Of A Mesophilic Strain Mcontrasting
confidence: 40%
See 2 more Smart Citations
“…S-2). This phenotype is different from several previously described xylanfermenting thermophiles such as C. thermolacticum (Le Ruyet et al, 1985) and C. clariflavum (Sizova et al, 2011).…”
Section: Identification and Characterization Of A Mesophilic Strain Mcontrasting
confidence: 40%
“…has a great potential for value-added products production from cellulose (Sizova et al, 2011;Yang et al, 2015), while most of the reported studies using hemicellulose compounds of lignocellulosic biomass as a fermentation substrate have been focused on ethanol or hydrogen production rather than on butanol (Tolonen et al, 2011). However, few wild-type strains are known to produce butanol from cellulose or xylan via simultaneous saccharification and fermentation, leaving a need for development of one-step strategies for biobutanol production from lignocellulosic materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermomonospora sp. Cerrena globosum and Aspergillus phoenicus) and bacteria (Bacillus, Bacteroides ovatus, Clostridium clariflavum) are capable of degrading xylans (Sunna and Antranikian, 1997;Abdel-Sater, 2001;Sizova et al, 2011 ). The hemicelluloses are degraded to CO 2 , H 2 O, cell biomass and various small carbohydrate molecules like monomers and dimers.…”
Section: Introductionmentioning
confidence: 99%
“…This is because there are indications that some of the uncultivated species may be involved in a variety of systemic diseases (4,20,44) and likely play an important role in the function of the oral microbial community. We have shown that some previously uncultivable microorganisms can be isolated by mimicking natural growth conditions, using in vivo incubation devices (25,30,34) or via enrichments (17,46,47), and also developed a method for single-cell long-term incubations (S. Buerger et al, submitted for publication). The main objective of this study was to apply these different approaches to the cultivation of oral microorganisms, assess their relative merits, and isolate new species from the list of presently uncultivated taxa.…”
mentioning
confidence: 99%